Dynamic somite cell rearrangements lead to distinct waves of myotome growth - Stellabotte, Frank (2007)
The myogenic precursors responsible for muscle growth in amniotes develop from thedermomyotome, an epithelium at the external surface of the somite. In teleosts, themyogenic precursors responsible for growth have not been identified. We have usedsingle cell lineage labeling in zebrafish to show that anterior border cells of epithelialsomites are myogenic precursors responsible for zebrafish myotome growth. These cellsmove to the external surface of the embryonic myotome and express the transcriptionfactor Pax7. Some remain on the external surface and some incorporate into the fastmyotome, apparently by moving between differentiated slow fibres. The posterior cellsof the somite, in contrast, elongate into medial muscle fibres. The surprising movementof the anterior somite cells to the external somite surface transforms a segmentallyrepeated arrangement of myogenic precursors into a medio-lateral arrangement similar tothat seen in amniotes.